Analisis Perilaku Pencarian Informasi Mahasiswa Ilmu Perpustakaan Menggunakan Model Ellis - Alfi Dalillah Aulia. S; Dina Mei Sari; Feny Arsela; Siti Fauziah; Franindya Purwaningtyas (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
In searching for information, students themselves are required not only to be successful in searching for information, but also to find quality information and its validity can be accounted for. The existence of the need for information makes many people to obtain information in various ways. The need for information also raises human actions and behavior in obtaining and seeking information. This study uses a qualitative research approach. In terminology according to Baydan and Taylor, a qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words. This research results that students perform information search to meet their information needs. Particularly the need for academic information, such as lecture assignments given by lecturers as well as to fulfill information needs about the basic theory of practicum. Keywords: Information Search Behavior, Student, Ellis Model